Follicle stimulating hormone producing (FSH) cells of buffalo-A histological, immunocytochemical and ultrastructural study - KHAN, MASSARAT; SAIGAL, R P; SETHI, R S (The Indian Journal of Animal Sciences, 2011)
Buffaloes (56) of either sex, of different age groups and in different phases of reproductive cycle were used to deternline the structure, localisation and distribution pattern of the FSH cells in the pars distalis. The FSH cells as demonstrated by differential staining, immunohistochemical and electronmicroscopy were variably round, ovoid and spindle shaped with processes. These cells had eccentrically placed nuclei usually round, oval, irregularly triangular or oblong/elongate and horse shoe shaped and had fine lightly stained, euchromatin material with fewer clumps and one or two prominent nucleoli. The estimated average diameter of the cells was 8.3Â±O.1 flm with a maximum of 106 fJID. Â